A180 IMPROVED RENAL LABORATORY PARAMETERS IN CHB PATIENTS TREATED WITH TAF COMPARED WITH TDF. (1st March 2018) - Wong, F; Khan, M; Agarwal, K; Furusyo, N; ,; Hwang, J; Flaherty, J; Kim, K
Abstract: Background: Tenofovir Disoproxil Fumarate (TDF) treatment results in high rates of viral suppression with no described resistance; however its use has been associated with a deterioration in bone mineral density and eGFR over time. TAF, a novel prodrug of tenofovir (TFV), has better stability in plasma resulting in lower systemic TFV exposures than TDF. Phase 3 studies of TAF in CHB demonstrated lower declines in eGFR compared to TDF over 48 weeks of treatment. Aims: Here, we further characterize the clinical renal benefits of TAF compared to TDF. Methods: In two identically-designed Phase 3 studies of TAF (Study 110 in HBeAg positive and Study 108 in HBeAg negative patients), patients were randomized 2:1 to TAF 25 mg QD or TDF 300 mg QD, each with matching placebo, and treated for 96 weeks. After Week 96, patients receive open label TAF for 48 weeks. Renal parameters including eGFR calculated by Cockcroft-Gault and CKD-EPI were evaluated throughout the study period. Chronic kidney disease (CKD) staging was categorized according to the NKF KDOQI guidelines (Stage 1: eGFR ≥ 90ml/min; Stage 2: eGFR 60–90 ml/min; Stage 3 eGFR 30–59 ml/min). Evaluated risk factors for kidney disease included older age and comorbidities of hypertension, cardiovascular disease and diabetes. Multivariate analysis was performed using backwards stepwise approach. Results: Baseline demographics between TAF and TDF groups in both studies were generally balanced for risk factors for kidney disease. At week 48, patients treated with TAF had smaller changes in creatinine (median change 0.01 mg/dL for TAF and 0.02 mgdL for TDF; p=0.012) and eGFRCG (median change -1.2 mL/min for TAF and -5.4 mL/min for TDF; p<0.001) during 48 weeks of treatment. The number of patients who had >25% creatinine clearance reductions was also greater in the TDF arm versus the TAF arm (14.5% vs 8.7%, p=0.002). Using the stages of CKD, a higher percentage of patients treated with TDF had one or more stage worsening in renal function at Week 48 (10.2% vs 6.5%; p=0.06). Among patients at highest risk for kidney disease (older age and comorbidities of hypertension, cardiovascular disease or diabetes), significantly more patients had worsening of renal function in TDF treated patients compared to TAF treated patients.Multivariate analysis of worsening renal function by CKD stage identified higher baseline eGFR, male gender, and Age > 50 as Independent predictors. Conclusions: In patients with CHB, TAF therapy is associated with improvement of renal safety versus TDF. The benefits of TAF may be particularly evident in patients at higher risk of GFR decline. Funding Agencies: Gilead Sciences, Inc.